Pengaruh Kompetensi Karyawan dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. M - Mulya, Galardia Orva; Tuhagana, Aji; Handayani, Dwi Epty (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Human resources are an important part of the business, so companies provide opportunities to develop the potential of their human resources to maximize employee performance, to be able to create maximum employee performance cannot be separated from the competencies possessed and work environment conditions in an organization where to work. The research was conducted to determine the effect of employee competence (X1) and work environment (X2) on employee performance (Y) at PT. M. Quantitative methods were used in this study with multiple regression analysis and using SPSS 24 for data processing, primary data sources were obtained by distributing questionnaires to employees of PT. M. The population selected for the study were all employees of PT. M totaling 230 with a sample of 146 employees using the Slovin formula used as a sampling technique. The results obtained are that there is a partial effect of employee competence on the performance of PT. M employees of 0.372 or 37.2%, there is a partial effect of the work environment on the performance of PT. M employees of 0.523 (52.3%) and there is a simultaneous effect of employee competence and work environment on the performance of PT. M employees of 0.663 (66.3%) and the remaining 33.7% are influenced by other variables.